PERKEMBANGAN KOGNITIF ANAK DALAM PERSFEKTIF PENDIDIKAN ISLAM - Suharnis, Suharnis (Musawa: Journal for Gender Studies, 2021)
Children's education begins from family (household) where they are influenced by what their parents do by imitating and learning. So, children’s cognitive development is inseparable from the family environment. Children’s development in cognitive theory shows the cognitive skills in the form of perception, learning process, attention, language skill, and emotion. These all are implicated in children’s behavior regarding the cognitive development process in capturing, assessing, comparing, and responding to a stimulus before reacting. An individual receives a stimulus and then performs the cognitive process before reacting to the occurring stimulus. This process includes procedures for obtaining information, presenting, and transforming the information as knowledge. This knowledge reflects an indication of children’s behavior and attitude. Therefore, children’s cognitive development in psychological view is categorized into four: the sensorimotor stage, preoperational stage, concrete operational stage, and formal operational stage.